From noncovalent chalcogen-chalcogen interactions to supramolecular aggregates: experiments and calculations - Gleiter, Rolf; Rominger, Frank (Chemical reviews, 2018)
This review considers noncovalent bonds between divalent chalcogen centers. In the first part we present X-ray data taken from the solid state structures of dimethyl- and diphenyl-dichalcogenides as well as oligoalkynes kept by alkyl-sulfur, -selenium, and -tellurium groups. Furthermore, we analyzed the solid state structures of medium sized (12-24 ring size) selenium coronands and medium to large rings with alkyne and alkene units between two chalcogen centers. The crystal structures of the cyclic structures revealed columnar stacks with close contacts between neighboring rings via noncovalent interactions between the chalcogen centers. To get larger space within the cavities, rings with diyne units between the chalcogen centers were used. These molecules showed channel-like structures in the solid state. The flexibility of the rings permits inclusion of guest molecules such as five-membered heterocycles and aromatic six-membered rings. In the second part we discuss the results of quantum chemical calculations. To treat properly the noncovalent bonding between chalcogens, we use diffuse augmented split valence basis sets in combination with electron correlation methods. Our model substances were 16 dimers consisting of two Me-X-Me (X = O, S, Se, Te) pairs and dimers of Me-X-Me/Me-X-CN (X = O, S, Se, Te) pairs. The calculations show the anticipated increase of the interaction energy from (Me-O-Me)2 (−2.15 kcal/mol) to (Me-O-Me/Me-Te-CN) (−6.59 kcal/mol). An analysis by the NBO method reveals that in the case of the chalcogen centers O and S the hydrogen bridges between the molecules dominate. However, in the case of Se and Te the major bonding between the pairs originates from dispersion forces between the chalcogen centers. It varies between −1.7 and −4.0 kcal/mol.
Gesehen am 03.05.2019